1968
DOI: 10.1039/tf9686403288
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced predissociation in the gas phase. Photolysis of methanol at 1849 Å

Abstract: The methanol photodecomposition quantum yield increases with the addition of different foreign gases (alkanes, rare gases, C 0 2 , SF6). Whereas the methanol absorption spectrum presents a continuum in the 1850 8, region, the added gas effect implies that collisions are involved in reaching the dissociative state. This apparent contradiction between photochemical and spectroscopic data leads to the postulate of the existence of a collision-induced predissociation. The efficiency of the different gases in promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

1971
1971
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
4
13
1
Order By: Relevance
“…It is unclear from these results which set of branching ratios gives the best overall match to the relative abundances observed in Sgr B2(N). The set of branching ratios favoring the methoxy channel agrees qualitatively with gas phase laboratory measurements, which determined the overall branching fraction for the combined CH 3 O and CH 2 OH channels to be ∼0.75 (Hagege et al 1968). To our knowledge, no gas phase or condensed phase laboratory measurements have yet distinguished between these two channels through direct measurements of the products.…”
Section: Influence Of Methanol Photodissociation Branching Ratiossupporting
confidence: 78%
“…It is unclear from these results which set of branching ratios gives the best overall match to the relative abundances observed in Sgr B2(N). The set of branching ratios favoring the methoxy channel agrees qualitatively with gas phase laboratory measurements, which determined the overall branching fraction for the combined CH 3 O and CH 2 OH channels to be ∼0.75 (Hagege et al 1968). To our knowledge, no gas phase or condensed phase laboratory measurements have yet distinguished between these two channels through direct measurements of the products.…”
Section: Influence Of Methanol Photodissociation Branching Ratiossupporting
confidence: 78%
“…So that OH radicals react with methyl radicals to produce methanol. However, we were not able to detect methanol in this work because as we have confirmed, UV irradiation (k = 185 nm) decomposes methanol through photodecomposition [23]. At high OH radical concentration, the methanol formed in the initial stage, undergoes further reaction with OH radicals to form oxygenated compounds such as formaldehyde (CH 2 O) and acetic acid (C 2 H 4 O 2 ), as reported by Ogura et al [9].…”
Section: Resultssupporting
confidence: 58%
“…In the first series, 11 Torr of 2-propanol was photolyzed in the presence of up to 1 atm of CO,. Carbon dioxide was chosen because Hagege et al (7) found that it was the most effective addend in increasing For personal use only. amount of CF, which has a small but finite study and the previously determined behavior vapor pressure at -196 "C. Again the rates of of this substrate and methanol in direct and formation of all products remain constant sensitized photolysis would indicate that the within experimental error or decline with the primary decomposition may proceed by two exce~tion of R(CH,COCH,).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hagege et al (7) reported that in the direct photolysis of CH,OH at 1849 A, added inert gases increased the decomposition quantum yields. These workers suggested that this enhancement occurs through a collision induced predissociation.…”
Section: Introductionmentioning
confidence: 99%